​The Broadcaster’s Catacombs: Looking for Literature in a Dutch Listings Magazine (De radiogids 1929–1941) - Jasper Schelstraete (Journal of European Periodical Studies, 2017)
As soon as radio became a mass medium in the 1920s and 1930s, broadcasting organizations aired programmes on literary topics. This article explores the function of literature in De radiogids, the weekly periodical of the Dutch socialist broadcaster VARA. Focusing on the pre-war period, the article shows that literary radio programmes received little attention in De radiogids, despite the efforts of literary programme maker Martien Beversluis to establish a literary feature in the magazine. Although these findings suggest that literary radio programmes were of little interest to the VARA, De radiogids contains valuable cultural-historical sources concerning the relationship between radio and literature in the interwar period.